SMIF Model With Maqashid Sharia-Based - Alhifni, Anas; Ahwarumi, Biyati (Jurnal Iqtisaduna, 2018)
Islamic microfinance institution is financial institution that is more oriented to the middle and lower community, its existence is for all religions and its role should be further optimized to provide welfare to members and community in general, this paper aims to explain the basic philosophy of Islamic microfinance institution and how the concept of Islamic microfinance institution in accordance with maqashid sharia values. The method used is qualitative method withanalysis techniques of data content analysis.Result of this article shows that the fundamental difference between Islamic microfinance institution and conventional finance institutionfound in the philosophy of moral values in accordance with texts of the Al-Quran and hadith. As maqashidsyariah-based SMIF financial institution that can guarantee every product that is able to provide benefits for people to reach Fallah or welfare, such as prioritizing profit sharing products, and keep the goal as business and social financial institution.